2018
DOI: 10.3390/molecules23030600
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trifluoromethylcoumarinyl Urea Derivatives: Synthesis, Characterization, Fluorescence, and Bioactivity

Abstract: A series of novel trifluoromethylcoumarinyl urea derivatives were designed, synthesized, and characterized by 1H-NMR, 13C-NMR, and HR-ESI-MS. The fluorescence spectra of the target compounds were recorded. The spectra show that most of the title compounds glow green with λmaxem of 500–517 nm, while compounds 5r, 5s, 5u, and 5l (compounds named by authors) glow violet with λmaxem of 381–443 nm. Moreover, the herbicidal and antifungal activities of the synthesized compounds were evaluated for their potential use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Thus, the desirable properties of next-generation antimicrobials should include broad-spectrum action and high efficacy toward pathogens but low toxicity to humans and should pose no risk of bioaccumulation. Recently, several diarylureas analogues of TCC were reported as antibacterial [ 18 ] and antifungal agents [ 19 ] bearing pentafluorosulfanyl and trifluoromethylcoumarine groups, respectively. As small molecules, their design should take into account a good oral bioavailability, following the “Lipinski’s rule of drug-likeness”, also named “the Rule of 5” (Ro5) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the desirable properties of next-generation antimicrobials should include broad-spectrum action and high efficacy toward pathogens but low toxicity to humans and should pose no risk of bioaccumulation. Recently, several diarylureas analogues of TCC were reported as antibacterial [ 18 ] and antifungal agents [ 19 ] bearing pentafluorosulfanyl and trifluoromethylcoumarine groups, respectively. As small molecules, their design should take into account a good oral bioavailability, following the “Lipinski’s rule of drug-likeness”, also named “the Rule of 5” (Ro5) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, second absorption band which can observed at 343-352 nm was attributed as higher intensity compared (ε =62200 -82200 M -1 cm -1 ) to the first absorption band. It is due to the electronic transition produced from excitation of unsaturated moiety in a molecular structure [27]. Plus, excitation of π electrons from lower to higher energy levels by several unsaturated chromophores such as aromatic and carbonyl moieties was responsible for the transition [28].…”
Section: V(c-h) V(c=o) V(c=n)mentioning
confidence: 99%
“…In this review, we will focus our attention on TCC, a small molecule also named 3,4,4′-trichlorocarbanilide that belongs to the class of diarylures or bis-arylureas. This interesting class of compounds has been recently reviewed by our research group as anticancer agents [ 6 ], and then, due to their multiple actions [ 7 , 8 , 9 , 10 , 11 ], they were also suggested for repositioning to antimicrobial agents and/or potential treatment for new pandemics, as COVID-19 [ 12 , 13 ]. TCC is a common ingredient in personal care products, especially dermal cleaning products such as antibacterial bar/Liquid soaps, body lotions, deodorants, detergents, medical disinfectants, aftershave soaps, hand sanitizers, toothpaste, handwash and mouthwash, body washes, cleansing lotions, baby teethers and wipes for its sanitizing properties and detergents [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will focus our attention on TCC, a small molecule also named 3,4,4trichlorocarbanilide that belongs to the class of diarylures or bis-arylureas. This interesting class of compounds has been recently reviewed by our research group as anticancer agents [6], and then, due to their multiple actions [7][8][9][10][11], they were also suggested for Since its advent in 1957 [22], TCC has been produced and used on a large scale, and its consumption from personal care products in the United States reached 500,000-1,000,000 pounds per year [23]. The 2013-2014 National Health and Nutrition Examination Survey showed that 36.9% of the urine samples in the United States (U.S.) contained TCC [24].…”
Section: Introductionmentioning
confidence: 99%